1994
DOI: 10.1111/j.1432-1033.1994.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies for the Immunochemistry of the Human β3‐Adrenergic Receptor

Abstract: Based on the amino acid sequence deduced from the recently cloned human P3-adrenergic receptor (hup3AR) gene, polyclonal antibodies were prepared against synthetic peptides, corresponding to regions of huP3AR presumed to be exposed at the outer or the inner side of the membrane on the basis of the putative three-dimensional structure of the previously characterized /31 and P2 adrenergic receptors. Affinity-purified antibodies directed against N-terminal, extracellular or intracellular loops and C-terminal pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
3
33
1
2
Order By: Relevance
“…Possibly, this re¯ects clustering of b 3 -adrenoceptors in sympathetically innervated cells. Furthermore, it is noteworthy that the staining pattern obtained in gall bladder was quite different from that reported in a previous study 23 using a polyclonal anti-peptide antibody. In the latter report, staining was associated primarily with arteriolar vascular smooth muscle cells, with negligible staining in the lamina propria.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Possibly, this re¯ects clustering of b 3 -adrenoceptors in sympathetically innervated cells. Furthermore, it is noteworthy that the staining pattern obtained in gall bladder was quite different from that reported in a previous study 23 using a polyclonal anti-peptide antibody. In the latter report, staining was associated primarily with arteriolar vascular smooth muscle cells, with negligible staining in the lamina propria.…”
Section: Discussioncontrasting
confidence: 50%
“…Data describing the immunohistochemical localisation of the b 3 -adrenoceptor has been limited to a single study using an anti-peptide polyclonal antibody, 23 which detected the receptor only in human gall bladder, a tissue that exhibits a relatively high level of b 3 -adrenoceptor mRNA. 17,19 The relative lack of sensitivity of this approach may be due to the dif®culty of producing a suitable high af®nity antibody using a short polypeptide immunogen.…”
mentioning
confidence: 99%
“…Two studies also examined localization of ␣ 1 ARs in native human smooth muscle cells and found internal as well as membrane-bound populations of ␣ 1a AR (Hrometz et al, 1999;Mackenzie et al, 2000). This is similar to the situation for the ␣ 2 ARs, where ␣ 2A -and ␣ 2B ARs are predominantly surface localized, whereas the ␣ 2C AR is predominantly intracellular (von Zastrow et al, 1993;Wozniak and Limbird, 1996;Daunt et al, 1997) but contrasts with ␤ARs, which are surface localized (Guillaume et al, 1994;Barak et al, 1997;McLean and Milligan, 2000).…”
mentioning
confidence: 61%
“…The ␤ 3 -receptor plays a major role in lipolysis but the role and distribution of ␤ 3 -receptors in other specific sites have not been extensively studied. Tissue distribution studies have demonstrated the presence of ␤ 3 -receptors not only in adipose tissues but also in human gall bladder and more recently in colon, prostate, and skeletal muscle (9)(10)(11). In addition, ␤ 3 -receptor stimulation has been recently demonstrated to elicit vasorelaxation of rat aorta through activation of NO synthase and the subsequent increase in tissue levels of cGMP (12).…”
mentioning
confidence: 99%